2019
DOI: 10.1016/j.chest.2018.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Use and Respiratory Morbidity in COPD

Abstract: BACKGROUND: Aspirin use in COPD has been associated with reduced all-cause mortality in meta-regression analysis with few equivocal studies. However, the effect of aspirin on COPD morbidity is unknown.METHODS: Self-reported daily aspirin use was obtained at baseline from SPIROMICS participants with COPD (FEV 1 /FVC < 70%). Acute exacerbations of COPD (AECOPD) were prospectively ascertained through quarterly structured telephone questionnaires up to 3 years and categorized as moderate (symptoms treated with ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…129 Daily use of aspirin is associated with a lower incidence of COPD exacerbations, less dyspnea, and a higher quality of life. 130 However, aspirin plus ticagrelor antiplatelet treatment did not work in about one-third of COPD patients without a history of CVD. 131 Calcium channel blockers.…”
Section: Potential Pulmonary Risks For Patients With Cad When Using D...mentioning
confidence: 99%
“…129 Daily use of aspirin is associated with a lower incidence of COPD exacerbations, less dyspnea, and a higher quality of life. 130 However, aspirin plus ticagrelor antiplatelet treatment did not work in about one-third of COPD patients without a history of CVD. 131 Calcium channel blockers.…”
Section: Potential Pulmonary Risks For Patients With Cad When Using D...mentioning
confidence: 99%
“… 26 These agents can also contribute to delaying the progression of emphysema, 27 improving dyspnea and quality of life in patients. 28 Furthermore, angiotensin-converting enzyme inhibitor (ACEI) / angiotensin receptor block (ARB) have also been proposed to display a beneficial effect on the risk of cardiovascular events. These drugs may also potentially delay the progression of emphysema while improving the lung function, 29 , 30 with dual cardiorespiratory protective properties.…”
Section: Copd and Cardiovascular Diseases (Cvd)mentioning
confidence: 99%
“…The authors found a significant reduction in the hazard of all-cause mortality by about 30% (HR: 0.71; 95% CI: 0.60, 0.84) [22]. Fawzy et al, 2018, published study findings from 1698 COPD patients who used aspirin for about one month [23]. The authors found that there was a non-significant reduction in the hazard of dyspnea by about 12% (HR: 0.98; 95% CI: 0.79, 1.21) [23].…”
Section: Main Findings Of Each Studymentioning
confidence: 99%